Wave splitting and double-slit like interference by a pseudochiral metamaterial slab. (26th June 2015) - Chang, Po-Han; Kuo, Chih-Yu; Chern, Ruey-Lin
Abstract: We investigate the phenomena of wave splitting and double-slit like interference by a pseudochiral metamaterial slab. Due to the anomalous dispersion associated with the particular form of magnetoelectric couplings in the pseudochiral media, there exist two elliptically polarized eigenwaves with the Poynting vectors directed in different directions. A wave incident from vacuum onto a pseudochiral slab will split into two waves even at normal incidence. Illuminated by a point like source, two secondary waves emerge on the back side of the slab, which in turn give rise to two spherical like waves that propagate in the forward direction. The two secondary waves then form an interference pattern that resembles the light wave passing through double slits. These features are illustrated with the Gaussian beams based on the Fourier integral formulation.